Answer: Hello there!
we know that the ratio of the pieces is 1:3:6
this means that the longest one has 3 times the length of the middle one and 6 times the length of the shortest.
we also know that the longest piece is 2.5 feet longer than the shortest piece, and we want to find the length of the original piece.
ok, let's define L as the length of the longest piece, M for the middle one and S for the shortest piece; then:
1) L - S = 2.5
2) L = 6*S
3) L = 3*M
we could replace the second equation into the first equation and get:
L - S = 2.5 ft
6S - S = 2.5 ft
5S = 2.5 ft
S = 2.5 ft/5 = 0.5 feet
now we can replace the value of S in the second equation and get the value of L.
L = 6*S = 6*0.5 ft = 3ft
and now we can replace the value of L in the third equation and get the value of M
L = 3M
3ft = 3M
M = 3ft/3 = 1ft
then L = 3ft, M = 1ft and S = 0.5ft
then the total lenght is L + M + S = 4.5 ft